3D game textures : create professional game art using photoshop - Ahearn, Luke (Amsterdam ; Boston : Focal Press/Elsevier, 2012)
Machine generated contents note: Introduction Textures Art Theory Breaking the world down visually Recreating the world visually in Photoshop Art as applied to CG applications Shaders and Materials Shader vs. Material What is a material system Nodes Node Input Node types and functions Material Examples Diffuse Specular Ambient Reflection real and faked Refraction Transparency Bump/ Displacement/ Normal mapping Specialized Materials; Skin etc. Creating Complex Materials Metals Glass Wood Compound Materials
Includes index
Keywords: Adobe Photoshop; Computer games -- Programming; Computer graphics